Aggression perpetrators and victims of domestic violence - Stodulska-Blaszke, Aldona; Wójcicka, Anna (Current Problems of Psychiatry, 2011)
The aim of our work is to obtain data about families of origin of perpetrators and victims of domestic violence and an analysis of the relationships between the occurrence of violence in families and generational varieties presented by the aggressiveness of the perpetrators and victims in adulthood. Study group consisted of 20 women - victims of violence and 20 male perpetrators of domestic violence. All persons have agreed to undergo psychological testing research. All women participated in the psychotherapy group for victims of domestic violence. The male subjects were required to participate in the anger management group. The following research tools were used: The Hostility – Gild Inventory A.H. Buss and A. Durkee, and enviromental survey of own design. Group of offenders were characterized by generally much higher rates of overall aggression as well as different types of aggression, than a group of victims. Significant correlations occurred between the groups with regard to physical aggression, indirect aggression, negativism, verbal aggression. Among the victims there is an association between alcohol abuse by the father and indirect aggression, irritation, aggression and general aggression factor. The use of sanctions in the form of childhood beatings had a statistically significant impact on the level of irritation of the victims disclosed in their adult life. Experiencing domestic violence from the family or father did not affect development of the guilt by preparators. Understanding the relationships between different types of aggression and the information about the family of origin of victims and perpetrators of violence, contribute to better knowledge and understanding of their behavior and understand their relationship.